1997
DOI: 10.1093/oxfordjournals.alcalc.a008318
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Cerebellar Nitric Oxide Synthase by Ethanol in Vitro

Abstract: The N-methyl-D-aspartate receptor/nitric oxide synthase (NOS)/guanylate cyclase pathway, which plays a crucial role in synaptic plasticity in the brain, is modulated by ethanol. We studied the effect of ethanol in vitro on NOS in rat cerebellum and showed that ethanol (25-200 mM) inactivated NOS in a dose-dependent manner. This inactivation was prevented by the biopterin cofactor tetrahydrobiopterin (BH4) as well as by L-arginine, a NOS substrate, but not by NADPH. These results suggest that ethanol reduces NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…0.05) inhibited NOS activity when assayed in the absence of exogenous BH4. A number of studies have demonstrated the essential role of exogenous BH4 in optimal assay of NOS activity [8,14,16]. Fataccioli et al [16] also observed a similar inhibitory effect of ethanol (25-200 mM ) on NOS in the cerebellum, and this inhibition could be alleviated by the addition of BH4 as well as L-arginine, the substrate for NOS.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…0.05) inhibited NOS activity when assayed in the absence of exogenous BH4. A number of studies have demonstrated the essential role of exogenous BH4 in optimal assay of NOS activity [8,14,16]. Fataccioli et al [16] also observed a similar inhibitory effect of ethanol (25-200 mM ) on NOS in the cerebellum, and this inhibition could be alleviated by the addition of BH4 as well as L-arginine, the substrate for NOS.…”
Section: Discussionmentioning
confidence: 92%
“…A number of studies have demonstrated the essential role of exogenous BH4 in optimal assay of NOS activity [8,14,16]. Fataccioli et al [16] also observed a similar inhibitory effect of ethanol (25-200 mM ) on NOS in the cerebellum, and this inhibition could be alleviated by the addition of BH4 as well as L-arginine, the substrate for NOS. Besides serving as a cofactor for NOS, BH4 is also an important cofactor for hydroxylase of three aromatic L-amino acids responsible for the synthesis of catecholamines and serotonin [24].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Cyclic GMP activates cGMPdependent protein kinase, which phosphorylates a number of intracellular proteins, including several transcription factors (Gertzberg et al, 2000;Gudi et al, 1996;Mitani et al, 2000), thereby effecting gene expression (Shibata et al, 1998). Ethanol has been described to both inhibit (Fataccioli et al, 1997;Zima et al, 1998) and stimulate (Fitzgerald et al, 1995;Shi et al, 1998) NO pathways, but the role of NO in ethanol-induced effects is not clearly established. This study was undertaken to determine whether some of the effects of ethanol on mAChRs involve NO pathways.…”
mentioning
confidence: 99%